Two new water beetles from the South African Cape (Coleoptera, Hydraenidae) - Bilton, David T. (Zootaxa, 2016)
Pterosthetops nitidus sp. nov. and Oomtelecopon namaqum sp. nov. are described from the Western and Northern Cape Provinces of South Africa respectively. Diagnostic notes are provided for each species, together with details of occupied microhabitats.